FunHoMic: A Marie Skłodowska-Curie Innovative Training Network for the study of the Fungus-Host-Microbiota interplay. Issue 12 (17th December 2021) - Cole, Nathaniel; Marsaux, Benoît; Rosati, Diletta; Delavy, Margot; Kosmala, Daria; Xie, Zixuan; Kaune, Ann-Kristin; Valentine, Marisa; Chakraborty, Sayoni; Kaur, Manjyot; Alaban, Leovigildo Rey; Morelli, Moran; et al.
Abstract : Introduction: The FunHoMic project is a Marie Skłodowska-Curie Innovative Training Network comprising 13 PhD students, 8 academic partners and 3 industry partnersaimingto understand the interplay between fungi, hostsand microbiota to improve prevention and treatment of fungal infections. Importance: About 2 billion people suffer fungal infections, which have a mortality rate close to that of malaria or breast cancer. Candida albicans has a high clinical and economic burden, making it of particular interest to the FunHoMic project. 70% of women experience at least one episode of vulvovaginal candidiasis ("thrush") during their lifetime; 8% suffer recurring infections. C. albicans may live as a commensal but can cause symptoms when the fungus-host-microbiota equilibrium is disrupted. Infections by C. albicans have a significant clinical impact, with fatalities in severe cases. Many factors are associated with C. albicans infections; intensive care, neutropenic and diabetic patients are most at risk of systemic infection. Rising antifungal drug resistance has led to certain C. albicans infections having no treatment option. Aim: The FunHoMic consortium combines projectson fungal pathogenesis, immunology, microbial ecology and'omics technologies to understand and exploit interactions between fungus, host and microbiota. Identification of novel bio markers on the fungal side such as genetic polymorphisms or on the host side such asmicrobiota profiles, metabolites and/or immune markers can lead to patient classification based on relative risk of infection. This could be the beginning of personalised management for fungal infections using preventive or therapeutic interventions like new antifungals, immune modulators or Live Biotherapeutic Products (LBPs). This project has received funding from the European Union's Horizon 2020 research and innovation programme under the MarieSklodowska-Curie grant agreement No 812969.